The use of economics in international trade and investment disputes / edited by Marion Jansen, Joost Pauwelyn and Theresa Carpenter. - Jansen, Marion; Pauwelyn, Joost; Carpenter, Theresa M. (Cambridge University Press, 2017)
Twenty-first-century trade agreements increasingly are a source of international law on investment and competition. With chapters contributed by leading practitioners and academics, this volume draws upon investor-state arbitration and competition/antitrust disputes to focus on the application of economics to international trade law and specifically WTO law. Written in an accessible language suitable for a broad readership while providing concrete insights designed for the specialist, this book will be of use to those active or interested in the related fields of trade disputes, competition law, and investor-state arbitration.
Cambridge University Press EBA 2025-26
Title from publisher's bibliographic system (viewed on 21 Apr 2017).
Keywords: International commercial arbitration.; Dispute resolution (Law); Foreign trade regulation.; Investments, Foreign.; World Trade Organization.